PRODUKSI DAN NILAI NUTRISI HIJAUAN JAGUNG MANIS (ZEA MAYSSACCHARATA) DENGAN PEMUPUKAN FOSFAT DAN INOKULASI MIKORIZA PADA KONDISI TANAH BERBEDA - Dwi Retno Lukiwati; Robert Djonggi Maruli Simanungkalit (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2003)
Rock phosphate (RP) fertilizer belongs to slow available source of phosphorus compared to superphosphate (SP), and mycorrhiza inoculation maybe a promising technique to overcome the problem. The symbiosis between mycorrhiza and Zea mays saccharaiaSturt in unsterilized soil has been less studied compared to sterilized soil. A greenhouse experiment was con• ducted on acid latosolic soiland low phosphorus availability. The experimental design was a factorial 2x2x3 in 3 replicates. The treatments were soil sterilization (unsterilized, sterilized), mycorrhiza inoculation (uninoculated, inoculated) and P fertilization (RP-10, RP-20, SP-36). All pots received fertilization of 200 kg N/ha (6 g urea/pot), 150 kg K20/ha (3.50 g KCl/pot) and 150 kg P20/ha of three kinds of P fertilizer source were RP-10 (21 g/pot), RP- 20 (10.50 g/pot) and SP-36 (6 g/pot). The latosolic soil was sterilized by autoclaf at 121°c for 15 minutes. Each pot contain 8 kg dry soil and inoculated by 40 g soil inoculum of Glomus manihotis according to the assigned treatment at the time of planting. Each pot contain 2 plants of Zea mays saccharata Sturt. Zea mays was cut at ground level at 6 wekks after planting and analyzed for dry matter (DM), N and P content. Dry matter production, N and P uptake with SP fertilizer were significantly higher compared to RP (RP-IO, RP-20) on both srreilized soil and unsterilized soil. Dry matter production, N and P uptake with SP fertilizer on sterilized soil were significantly higher compared to unsterilized soil, while RP fertilizers (RP-10, RP-20) were not significantly different. The DM production, N and P uptake of Zea mays were not significantly affected by the interaction.between the treatments of mycorrhiza inoculation, P fertilization and soil sterilization.